2013
DOI: 10.1007/978-3-642-36095-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Efficient and Strongly KI-Secure Hierarchical Key Assignment Schemes

Abstract: Hierarchical Key Assignment Schemes can be used to enforce access control policies by cryptographic means. In this paper, we present a new, enhanced security model for such schemes. We also give simple, efficient, and strongly-secure constructions for Hierarchical Key Assignment Schemes for arbitrary hierarchies using pseudorandom functions and forward-secure pseudorandom generators. We compare instantiations of our constructions with state-of-the-art Hierarchical Key Assignment Schemes, demonstrating that our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 27 publications
(59 reference statements)
0
58
0
Order By: Relevance
“…Many schemes in the literature provide each user with a single secret [3,11], the trade-off being that the amount of public information and derivation time may be substantial. In contrast, chain-based schemes require no public information but each user may require more than one secret [9,14,15]. In addition, chain-based schemes can achieve very strong security properties [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many schemes in the literature provide each user with a single secret [3,11], the trade-off being that the amount of public information and derivation time may be substantial. In contrast, chain-based schemes require no public information but each user may require more than one secret [9,14,15]. In addition, chain-based schemes can achieve very strong security properties [15].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, chain-based schemes require no public information but each user may require more than one secret [9,14,15]. In addition, chain-based schemes can achieve very strong security properties [15]. There are many different ways to instantiate a chain-based scheme for a given policy, each instantiation being defined by a chain partition of the partially ordered set that defines the policy.…”
Section: Introductionmentioning
confidence: 99%
“…Our first set of contributions is associated with the novel concept of a tree partition of an information flow policy, from which we define the notion of a forest-based cryptographic enforcement scheme for information flow policies. We prove results establishing how the total number of secrets to be issued to users varies with the structure of the forest and demonstrate that an instantiation of our scheme retains the security property of strong key indistinguishability introduced by Freire, Paterson and Poettering [21]. We design and analyze an efficient algorithm for computing a forest that minimizes the total number of issued secrets.…”
Section: Introductionmentioning
confidence: 84%
“…The trade-off with such schemes is that some users may require more than one secret in order to be able to derive all the required encryption keys. Subsequent work established that secure instantiations of such schemes are possible [20,21].…”
Section: Related Workmentioning
confidence: 99%
“…, κ xn , an adversary should not be able to distinguish between the key for a challenge node x (not a descendent of any x i ) and a randomly chosen key. Recently, Freire et al [15] suggested a new…”
Section: Key Assignment Schemesmentioning
confidence: 99%